2021
DOI: 10.1186/s43066-021-00108-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of directly acting anti-viral agents on immunological imprints in chronic HCV-4a patients: interleukin-10 and vascular endothelial growth factor genes expression level

Abstract: Background Hepatitis C virus infection is a global health challenge with Egypt being one of the highly affected countries. IL-10 has been suggested as a suitable marker to assess necroinflammation and to monitor the progression of liver damage. Vascular endothelial growth factor (VEGF) is a potent angiogenic factor playing a central role in many physiological as well as pathological processes. Several factors can be predictive of the response to treatment and achievement of SVR; some of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
3
3
0
Order By: Relevance
“…Supporting our hypothesis, previous studies showed that the circulating VEGF level is correlated with the stage of HCC and the highest VEGF levels are found in patients with metastasis [28,29]. In agreement with our results, previous studies showed an increase in serum level of VEGF in HCV-infected patients [30,31]. The upregulation of VEGF in HCV patients may affect the inflammatory pattern in these patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Supporting our hypothesis, previous studies showed that the circulating VEGF level is correlated with the stage of HCC and the highest VEGF levels are found in patients with metastasis [28,29]. In agreement with our results, previous studies showed an increase in serum level of VEGF in HCV-infected patients [30,31]. The upregulation of VEGF in HCV patients may affect the inflammatory pattern in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…Compelling with our results, we reported a significant increase in serum NF-кB, a potent proinflammatory cytokinin, in the sera of HCV-infected patients. Supporting our finding, A significant increase in proinflammatory cytokines was noted in HCV-infected patients [31,32]. Furthermore, chronic inflammation during HCV infection is thought to be responsible for HCC development via increased mutation rate in the regenerating hepatocytes [33].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results agreed with those published by Freekh et al [59] and Waked et al [60]. In chronic HCV patients, Naga et al [61] examined the impact of DAAs on immunological imprints, including blood cells.…”
Section: Discussionsupporting
confidence: 88%
“…One of the main causes of chronic liver disease, which progresses to progressive hepatic fibrosis and eventually cirrhosis and HCC, is chronic HCV infection [2] . The development of oral Direct-Acting Antivirals (DAAs), which directly block the HCV replication cycle and target three key HCV genome regions (NS3/4A protease, NS5A, and NS5B RNA-dependent polymerase) led to a significant advancement in HCV therapy [3] . Raouf et al [4] have documented the impact of numerous variables on the onset and course of disease, including genetic variants, host factors (age, sex, environment, and related medical conditions) and viral factors like viral genotype and viral load.…”
Section: Introductionmentioning
confidence: 99%